2021
DOI: 10.1002/anie.202110512
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Enrichment of Enzyme‐Instructed Assemblies in Cancer Cell Lysosomes Turns Immunologically Cold Tumors Hot

Abstract: Lysosome‐relevant cell death induced by lysosomal membrane permeabilization (LMP) has recently attracted increasing attention. However, nearly no studies show that currently available LMP inducers can evoke immunogenic cell death (ICD) or convert immunologically cold tumors to hot. Herein, we report a LMP inducer named TPE‐Py‐pYK(TPP)pY, which can respond to alkaline phosphatase (ALP), leading to formation of nanoassembies along with fluorescence and singlet oxygen turn‐on. TPE‐Py‐pYK(TPP)pY tends to accumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
41
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 89 publications
0
41
0
Order By: Relevance
“…In another work, Ding et al. reported turning immunologically cold tumors hot by LMP‐induced ENS [24] …”
Section: Targeting Lysosomementioning
confidence: 95%
See 1 more Smart Citation
“…In another work, Ding et al. reported turning immunologically cold tumors hot by LMP‐induced ENS [24] …”
Section: Targeting Lysosomementioning
confidence: 95%
“…In another work, Ding et al reported turning immunologically cold tumors hot by LMP-induced ENS. [24] 8. Targeting Nucleus Nucleus, which stores the genes of cells and acts as the control center of the cell, probably is the most important subcellular organelle.…”
Section: Targeting Lysosomementioning
confidence: 99%
“…The second strategy ( Ji et al, 2021 ; Wu et al, 2021 ) employs an enzyme-instructed self-assembly (EISA) approach. Alkaline phosphatases are highly expressed on the plasma membrane of many types of cancer cells and have been adopted as ELSA-promoting enzymes to induce LMP by mediating nano-aggregation ( Wang et al, 2016 ; Gao et al, 2020a ).…”
Section: Nano-aggregation-induced Lysosomal Membrane Permeabilizationmentioning
confidence: 99%
“…Py-Yp-Lyso had significantly higher cytotoxicity in Hela cells than in normal cells and inhibited tumor growth to 55.4% of that of control tumors at day 15 following the injection. Similarly, Ji et al ( Ji et al, 2021 ) constructed an LMP trigger called TPE-Py-pYK(TPP)pY, which was composed of three segments: tetraphenylethylene-pyride (TPE-Py) mainly for imaging, pYKpY (pY = phosphotyrosine) for self-assembly, and triphenylphosphine (TPP) for charge regulation and internalization. Treating Hela cells with TPE-Py-pYK(TPP)pY caused lysosomal destruction and high cytotoxicity.…”
Section: Nano-aggregation-induced Lysosomal Membrane Permeabilizationmentioning
confidence: 99%
“…Copyright 2021, Elsevier Ltd. d) Schematic illustration of nano-assembles inducing lysosomal membrane permeabilization to evoke ICD for turning cold tumor into hot. Reproduced with permission [58]. Copyright 2021, Wiley-VCH GmbH.…”
mentioning
confidence: 99%